Implementasi Representational State Transfer pada Sistem Administrasi Laporan Bulanan (Studi Kasus : Navila Resto) - Rocha Yulinar; Buce Trias Hanggara; Widhy Hayuhardhika Nugraha Putra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Navila Resto is a business dealing in food sector. This business that is founded in late 2018 performs monthly service and management evaluation. The evaluation is obtained through reports recapitulated by the restaurant's employees at the end of the month. The reports managed in the ledger need to be copied to Microsoft Word and Excel and sent through Whatsapp to be reported to the executives. It is highly inefficient and ineffective. Reports data processed by Navila keep increasing, causing difficulties in the data analysis and the reports are prone to be buried by new messages. From the aforementioned problems, a better development of administration information system for data management is required. This research aims to develop web-based and android-based administration information system through the use of CodeIgniter framework and Reactnative framework. The needs analysis shows that the system requirements include 17 functional needs and 1 non-functional need in total. The result of system functionality test through validation testing of the overall system function for the users is 100% valid. The system non-functionality test is done through System Usability Scale (SUS) method, which was obtained from the questionnaires filled by the employees of Navila Resto as the respondents. The test result is 72.1, with a category of acceptable and adjective ratings of OK.